Research on the Application of Digital Modeling in Inheriting Traditional Chinese Architectural Art — Taking the Design of the Lei Family Architecture as an Example - Liang, Weisha (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
With the progress of science and technology, digital modeling technology plays an increasingly important role in the protection and restoration of traditional architectural heritage. This paper discusses the application of digital modeling technology in the inheritance of Chinese traditional architectural art, especially taking the architectural design of style Lei family as an example, and analyzes how technology supports the preservation and revival of traditional architectural art. By using modern design software such as 3DMAX, Maya, rhinoceros and SketchUp, this study discussed in detail the specific application and effect of these tools in the digital modeling, restoration and display of styleray family buildings. The paper also examines the contribution of digital modeling technology to the restoration of architectural details, the reconstruction of historical data, public display and education promotion.